Grammarly’s Effectiveness in Enhancing English Writing: A Case Study of Vocational High School Students - Damayanti, Selma; Azizah, Siti (Institut Agama Islam Negeri Madura, 2024)
Many vocational high school students in Pamekasan, Indonesia, face difficulties in understanding and applying basic grammar rules, which leads to poor writing skills. Despite the increasing use of Automated Writing Evaluation (AWE) tools like Grammarly, there is limited research on their effectiveness in vocational educational settings. To address this gap, the study aims to evaluate the impact of Grammarly on improving the English writing skills of tenth-grade vocational students, focusing on areas where it offers the most significant benefits. A quantitative pre-experimental design, involving pre-tests and post-tests, was used to assess changes in students' writing proficiency, with descriptive statistics and t-tests employed for data analysis. The findings revealed that Grammarly significantly enhanced students' grammar and punctuation accuracy, though no substantial improvement was observed in overall writing quality. However, the tool proved effective in helping students identify and correct common errors, improving the clarity and coherence of their writing. Further research is recommended to explore the long-term effects of AWE tools like Grammarly in various educational contexts.